Prospective study on the significance of mucosal barrier dysfunction markers in assessing the effectiveness of the new strategy for treating food hypersensitivity in children - O.P. Pakholchuk; S.N. Nedelska (Zaslavsky O.Yu., 2018)
Background. Further search for the ways to correct the key links of food hypersensitivity (FH) skin symptoms remains perspective. Aim of the study was to evaluate pathogenetically grounded therapy of the skin FH symptoms in children. Materials and methods. From 2011 to 2016, after analyzing source medical records of the 1780 children aged 1 month to 18 years, 148 eligible patients were randomly divided into 2 groups of treatment. Group 1 (n = 88) was administered pathogenetically grounded therapy for 10 days, which was aimed at the correction of epidermal and mucosal barrier dysfunction; group 2 (comparison) received standard treatment. Results. Median and interquartile variation of the SCORing Atopic Dermatitis results in group 1 were statistically lower (p < 0.05). Exacerbations (U[79; 53] = 1492.5; p = 0.001) and duration of the skin symptoms persistence (U[79; 53] = 1516.5; p = 0.001) were rare as compared to the group 2. Children with onset of the symptoms before 12 months of age had better prolonged effect (p < 0.05). Assessment of the relative humidity of the skin enables to control and to predict the incidence and duration of the FH skin symptoms equally. Conclusions. Pathogenetically grounded therapy of the skin FH symptoms in children had both short- and long-term effects regardless of clinical phenotype of the rash.